The efficacy of intense pulse light among patients with skin type III-IV in acute facial acne: the Malaysian experience - Ismail, Adibah Hanim; Chin, Shih Choon; Ng, Michael Leong Toong; Kaur, Simerdip; Lakhbir Singh, Sarabdeep Singh; Mogan, Saruveish; Hatah, Ernieda (Malaysian Medical Association, 2021)
Twenty-seven adult patients, skin type III -V with mild to moderate acne, were recruited. IPL at wavelengths range of 420 - 600nm with triple pulses was administered every two weeks for a total of 3 sessions. Assessment of acne severity and improvement of treatment was based on Global Acne Grading System (GAGS), scoring before and after treatment for each session and patient satisfaction’s using a 5-item Likert scale range at the end of session three. Results: Of the 27 patients, 77.8% were female. Their ages group ranged from 18 to 35 years, and all patients had skin type III or IV. There were 14 mild acne patients and 13 moderate ones. There was a statistically significant improvement in mean acne severity score from 18.1± 4.3 at baseline to 14.3 ± 4.6 after two weeks post-IPL and 12.3 ± 4.9 after four weeks post-IPL. The result on satisfaction level of patients showed ‘satisfied’ in 3 patients, “very satisfied” in 5 patients; and, half of the patients (11) answered “fair” at the end of the study. Most patients tolerated well the procedure, and only 5 patients developed either post-inflammatory hyperpigmentation or skin hyperpigmentation. Conclusion: The IPL of wavelength of 400-600nm offers effective, safe, and well-tolerated treatment of mild to moderate acne lesions in Malaysians with skin types III-IV. The majority of subjects had a fair score on treatment satisfaction. It is recommended that reasonable expectations for clinical results be addressed with patients before hands to prevent over-expectation.